Analytical studies on woven fabrics' bagging performance affected by the material, yarn, and fabric parameters. Issue 5 (4th May 2017) - Movahed, Hamid; Hasani, Hossein; Hassanzadeh, Sanaz
Abstract: The present work focuses on investigating the bagging behavior of woven fabrics produced from viscose and polyester/viscose yarns. In this paper, the bagging deformation – in terms of different bagging parameters (bagging resistance, bagging fatigue, bagging hysteresis, and residual bagging hysteresis) – has been interpreted by fabric's physical and mechanical properties which were obtained from FAST system. The statistical analysis revealed that there is a significant correlation between the bagging parameters. Also, it was concluded that the samples' physical and mechanical properties correlate significantly with bagging parameters. Additionally, the effects of four different variables such as material type, spinning system, weave pattern, and weft density on bagging parameters have been studied. Considering the high correlations between all the bagging parameters, it was decided to analyze only the parameter bagging fatigue in this paper. The results showed that all the fabric variables except the parameter weft density have significant effects on bagging fatigue performance.